IMPLEMENTASI TAX HOLIDAY DALAM RANGKA PENINGKATAN FOREIGN DIRECT INVESTMENT (FDI) DANTENAGA KERJA DI INDONESIA - Kumalasari, Kartika Putri; Wicaksana, Achmad Chandra (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to determine the extent to which Tax holiday is implemented and how it impactsForeign Direct Investment (FDI) and the increase in labor in Indonesia and to find out the obstaclesthatmay be experienced in implementing Tax holiday policies in the three agencies, namely theDirectorate General of Taxes, the Policy Agency. Fiscal and Investment Coordinating Board.Researchers used qualitative research with a case study approach in accordance with the theory ofCresswell (2016). qualitative with a case study approach in accordance with the theory of Cresswell(2016). There are two sources of data, namely, primary data processed directly by researchers,sourced from interviews between researchers and three agency representatives from the DirectorateGeneral of Taxes, the Fiscal Policy Agency, and the Coordinating and Investment Board andsecondary data is data that is not processed directly by the researcher. related and supporting thisresearch. The results of this study indicate that the Tax holiday policy has been running according tothe PMK 150 / PMK.010 / 2018 regulations with the existence of Online Single Submission (OSS) inthis regulation which helps reduce the rate of administration in implementing Tax holiday policieswhich impact on the increase of Foreign Direct Investmentworkers in Indonesia, however there is still confusion in the interpretation of the PMK 150 /PMK.010 / 2018 regulations